Fish who could wish (The) - Bush, John (Brooklyn, New York : Kane/Miller Book Publishers, 1991)
A fish's wishes come true until the day he makes a foolish wish.
Keywords: Fishes-Fiction; Wishes-Fiction; Stories in rhyme